2021
DOI: 10.1111/all.15148
|View full text |Cite
|
Sign up to set email alerts
|

The value of the basophil activation test in the evaluation of patients reporting allergic reactions to the BNT162b2 mRNA COVID‐19 vaccine

Abstract: Background mRNA‐based COVID‐19 vaccines have been reported to induce hypersensitivity reactions (HSR) in a small number of individuals. We aimed to evaluate the real‐world incidence of the BNT162b2 mRNA COVID‐19 vaccine HSR and to determine the value of the basophil activation test (BAT) in the allergological workup of patients reporting these reactions. Methods We prospectively enrolled patients with a clinical history indicative of HSR to the BNT162b2 mRNA COVID‐19 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 40 publications
5
42
0
Order By: Relevance
“… 32 Wortmannin experiments also confirmed that basophil activation by PEG or BNT‐vaccine was mediated by IgE. 28 Some authors have claimed that a non‐IgE‐mediated mechanism is the cause of basophil activation, because IgE against PEG could not be found in the serum. 10 , 28 The lack of detection could be due to methodological problems in these assays, because a new dual cytometric bead assay (using PEGylated products) was able to demonstrate that samples of patients with PEG‐associated anaphylaxis were clearly positive for anti‐PEG‐IgE.…”
Section: Evaluation Of the Studiesmentioning
confidence: 85%
See 4 more Smart Citations
“… 32 Wortmannin experiments also confirmed that basophil activation by PEG or BNT‐vaccine was mediated by IgE. 28 Some authors have claimed that a non‐IgE‐mediated mechanism is the cause of basophil activation, because IgE against PEG could not be found in the serum. 10 , 28 The lack of detection could be due to methodological problems in these assays, because a new dual cytometric bead assay (using PEGylated products) was able to demonstrate that samples of patients with PEG‐associated anaphylaxis were clearly positive for anti‐PEG‐IgE.…”
Section: Evaluation Of the Studiesmentioning
confidence: 85%
“… 34 Experiments with the BAT showing a decrease in BNT‐vaccine‐induced basophil activation by preincubation with wortmannin might pose an argument for an IgE‐mediated immune response to SARS‐CoV‐2 spike proteins in patients with a previous SARS‐CoV‐2 infection. 28 BATs with spike peptides showed a slightly higher activation compared to baseline (below the cut‐off) in some patients with previous SARS‐CoV‐2 infection, which could be a hint for such a mechanism. 30 On the other hand, PEGylated compounds have the role of a solubilizer during the transition of the particles into the intracellular cytosol due to their hygroscopic properties, 35 which might influence unspecific detection or upregulation of surface markers on basophils in certain individuals.…”
Section: Evaluation Of the Studiesmentioning
confidence: 87%
See 3 more Smart Citations